Grouping modulation with different codes for improving performance in cVEP-based brain–computer interfaces - Wei, Qingguo; Gong, Huayun; Lu, Zongwu (Electronics letters, 2017)
A novel paradigm for building code modulated visual evoked potential (cVEP) brain–computer interfaces (BCIs) is proposed. The paradigm is based on grouping modulation of stimuli with different codes in order to increase the number of stimuli and resulting information transfer rate (ITR). In a single group, an original code and its circularly shifting codes are used for modulating 16 stimuli. To achieve good separability of stimuli, the original codes for different groups should have good autocorrelation and cross-correlation properties. A pair of Golay complementary series and an almost perfect autocorrelation sequence are used as the original codes to implement a three-group cVEP BCI with 48 targets. Four subjects participated in a simulated online experiment and a high ITR of 129.58 bits/min was achieved due to the sharp increase of the number of targets.